2015
DOI: 10.4209/aaqr.2014.09.0200
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Aerosol and Cloud Properties over Sindh Using MODIS Satellite Data and a HYSPLIT Model

Abstract: In this study, aerosols spatial, seasonal and temporal variations over Sindh, Pakistan were analyzed which can lead to variations in the microphysics of clouds as well. All cloud optical properties were analyzed using Moderate Resolution Imaging Spectroradiometer (MODIS) data for 12 years from 2001 to 2013. We also monitored origin and movements of air masses that bring aerosol particles and may be considered as the natural source of aerosol particles in the region. For this purpose, the Hybrid Single Particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 61 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…In addition, higher air temperatures in summer tend to hold more water vapors that feed aerosol to grow (Masmoudi et al, 2003), which might be the other reason causing higher AOD level. The similar seasonal variations were studied by Balakrishnaiah et al (2012) over India, Alam et al (2010Alam et al ( , 2014 and Sharif et al (2015) for Pakistan, and in China examined by Luo et al (2013) and Kang et al (2015). All these studies showed that the AOD values were higher due to the enhancement in urbanization and industrialization, dust storms, anthropogenic activities and salt particles blowing from the sea.…”
Section: Spatial and Temporal Variations Of Aod And Aesupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, higher air temperatures in summer tend to hold more water vapors that feed aerosol to grow (Masmoudi et al, 2003), which might be the other reason causing higher AOD level. The similar seasonal variations were studied by Balakrishnaiah et al (2012) over India, Alam et al (2010Alam et al ( , 2014 and Sharif et al (2015) for Pakistan, and in China examined by Luo et al (2013) and Kang et al (2015). All these studies showed that the AOD values were higher due to the enhancement in urbanization and industrialization, dust storms, anthropogenic activities and salt particles blowing from the sea.…”
Section: Spatial and Temporal Variations Of Aod And Aesupporting
confidence: 76%
“…Alam et al (2010Alam et al ( , 2014 have recently investigated that the AOD and cloud properties correlations changes with changing seasons in different regions of Pakistan. Also, Sharif et al (2015) examined that the correlations between AOD and cloud properties (same as the cloud parameters used in this study) were observed to be depended on the meteorological parameters for the regions over Sindh in Pakistan. Recently, Kang et al (2015) investigated the spatial and temporal correlations between AOD and cloud properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Makran coast region (south-east coast of Iran) shows significant differences between the 15-min and 60-min datasets (Figure 4). This area is particularly problematic for dust observation due to frequent cloud formation and high CWV content [29]. Near-shore convective cloud patterns obscure atmospheric dust soon after emission and the 60-min dataset is unable to recognize many dust emission events with an acceptable level of confidence.…”
Section: Seasonal Cloud Conditionsmentioning
confidence: 99%
“…Atmospheric aerosols are comprised of different types of suspended particles including dust, saline particles from seas, volcanic ashes and anthropogenic emissions (e.g., burning of fossil fuels). In recent decades, several research studies have been conducted stressing out the effects of airborne dust particles on Earth radiation budget, carbon cycle, formation of cloud condensation nuclei (CCNs) as well as precipitation, formation of cloud properties, human health and premature mortality (Crooks et al 2016;Giannadaki et al 2014;Han et al 2009;Shao et al 2011;Sharif 2015;Stafoggia et al 2016). Dust storms, typically taking place in arid and semiarid areas, are potentially capable of making these areas uninhabitable as well as damaging young crops and reducing visibility to the extent that both ground and aerial transportations are affected coupled with other undesirable economic impacts that ultimately make this a crucially important issue.…”
Section: Introductionmentioning
confidence: 99%